KEMAMPUAN BIOCHAR MEMEGANG AIR PADA TANAH BERTEKSTUR PASIR - S. Sutono; N. L. Nurida (Universitas Tribhuwana Tunggadewi, 2012)
Traditionally biochar is already used for different kinds of people activities such for cooking, cloth ironing. However, utilization of biochar in agriculture is limited only for pot media. Application of biochar in agriculture land is a carbon conservation technology due the long standing capacity in the soil. A laboratory study was conducted at soil physics laboratory of Soil Research Institute, Bogor using sandy soil. A factorial experiment with three factors was applied. The first factor was soil consisting of 20, 30, 40, 50, 60 and 92 percent of sand. The Second factor was three kinds of biochar: rice husk, palm oil, and cocoa skin fruit. The third factor was concentrations of biochar: 0, 10, 20 and 40 t/ha. Water holding capacity was measured by pF ceramic plate (pF1, pF 2, pF 2.54 and pF 4.2). The results indicated that biochar made from cacao skin fruit gave high pore aeration and increased number of water availability followed by made rice husk biochar and palm oil biochar